Watershed delineation on a hexagonal mesh grid. (June 2020) - Liao, Chang; Tesfa, Teklu; Duan, Zhuoran; Leung, L. Ruby
Abstract: Spatial discretization is the cornerstone of all spatially-distributed numerical simulations including watershed hydrology. Traditional square grid spatial discretization has several limitations including inability to represent adjacency uniformly. In this study, we developed a watershed delineation model (HexWatershed) based on the hexagon grid spatial discretization. We applied this model to two different types of watershed in the US and we evaluated its performance against the traditional method. The comparisons show that the hexagon grid spatial discretization exhibits many advantages over the tradition method. We propose that spatially distributed hydrologic simulations should consider using a hexagon grid spatial discretization. Highlights: First, our method resolves a decadal issue in watershed hydrology: the diagonal island effect. Because of that, no manual corrections are needed. Second, our method shows that spatially distributed hydrology models can be improved if the hexagon grid spatial discretization method is used. Third, our method provides a pathway to close the gap between regional and global scale hydrology simulations.